Prevalence of dementia in Egypt: a systematic review - Elshahidi MH (Dove Medical Press, 2017)
Mohamed H Elshahidi,1 Muhammad A Elhadidi,2 Ahmed A Sharaqi,1 Ahmed Mostafa,3 Mohamed A Elzhery1 1Faculty of Medicine, Mansoura University, Mansoura, 2Faculty of Medicine, Zagazig University, Zagazig, 3Faculty of Medicine, Sohag University, Sohag, Egypt Background: With the growing prevalence of dementia worldwide, two-third of the people with dementia are projected to be from the developing countries by 2050. Aim: This study reviews the literature regarding dementia prevalence in Egypt. Methods: Six databases were systematically searched from their dates of inception till July 2016. Studies published in English and reporting dementia prevalence among nonhospitalized individuals after clinical examinations were considered eligible. References were screened independently by two reviewers in two steps: 1) abstract screening and 2) full-text reviewing. In addition, quality of the included studies was assessed using the Newcastle–Ottawa scale. Results: Of the 1,630 references retrieved, six studies (n=28,029 participants) met our inclusion criteria. In all studies, dementia was ascertained using a three-phase survey (Phase I: screening, Phase II: clinical diagnosis, Phase III: laboratory investigations). The dementia prevalence ranged from 2.01% to 5.07%. Dementia increased with age, with the rapid increase among those aging ≥80. Also, its prevalence was higher among illiterate groups than among educated groups. Included studies were of low risk of bias. Conclusion: Dementia prevalence in Egypt demands including people with dementia in the health care system and promoting the awareness of dementia among the public. Also, more epidemiological studies in this field are needed. Keywords: aging, epidemiology, Alzheimer’s disease, vascular dementia